The Picaresque in Chinese and Hispanic American Narrative: A Comparative Study - Ding, Yiwen (2022)
This work describes traces of the picaresque novel in literature outside Europe by analyzing and comparing two novels from the perspective of the picaresque genre, one from Cuba, El Rey de La Habana, and the other from China, Leaving Home at 18. It is based on the criteria proposed by Fernando Cabo Aseguinolaza and has found that these two novels have characteristics of the picaresque genre despite the fact that in El Rey de La Habana these characteristics are more evident according to the referentialist orientation, while in the other one the picaresque character is more easily verified from the formal perspective.